Investigating global spread of Fusarium oxysporum f. sp. cubense race 4 isolates - Bailey, Wendy Camrodeen (Stellenbosch : Stellenbosch University, 2025)
Bailey, Wendy Camrodeen. 2024. Investigating global spread of Fusarium oxysporum f. sp. cubense race 4 isolates. Unpublished masters dissertation. Stellenbosch : Stellenbosch University [online]. Available: https://scholar.sun.ac.za/handle/10019.1/131567